Triglyceride Glucose Index Was a Predictor of 6-Month Readmission Caused by Pulmonary Infection of Heart Failure Patients - Licheng Shi; Jianan Liu; Xuanfeng Zhu; Tiantian Li; Jingli Wen; Xinyu Wang; Xu Qi (International Journal of Endocrinology)
Objectives. Insulin resistance is associated with the prognosis of heart failure (HF) patients. The triglyceride glucose (TyG) index is a simple marker of insulin resistance. However, it remains unclear whether the TyG index is associated with the incidence of readmission in patients with HF. Methods. We enrolled 901 patients with completed records on serum triglyceride and glucose in our study. The TyG index was calculated as log (fasting triglycerides (mg/dL) x fasting glucose (mg/dL)/2). There were 310 cases of readmission and the average TyG index was 7.8 ± 0.7. Restricted cubic spline was fitted to explore the linearity of TyG index associating with 6-month readmission of HF patients. Logistic regression analysis was performed to explore the association between TyG index quartile and the incidence of 6-month readmission. Results. Only the 6-month readmission was significantly different among TyG quartiles, and it was the highest (41.9%) in the lowest quartile (ranging 6.17∼7.36). the TyG index was nonlinearly associated with 6-month readmission (p for nonlinearity = 0.009), with the lower level of TyG index increasing the risk of 6-month readmission. Besides, multivariable logistic analysis showed that the lowest TyG quartile was associated with a higher incidence of 6-month readmission in the unadjusted model (odds ratio [OR] 1.74, 95% confidence interval [CI] 1.18–2.57; p=0.005), partially adjusted model (OR 1.82, 95%CI 1.22–2.72; p=0.004), and fully-adjusted model (OR 1.65, 95%CI 1.09–2.45; p=0.024). The association was consistent across gender and diabetes group. Conclusion. A lower TyG index independently increased the risk of 6-month readmission in HF patients, which could be a prognostic factor in heart failure.